2020
DOI: 10.1016/j.joca.2019.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of the first-in-class imidazoline-2 receptor ligand CR4056 in pain from knee osteoarthritis and disease phenotypes: a randomized, double-blind, placebo-controlled phase 2 trial

Abstract: Objective: CR4056 is a selective imidazoline-2 (I2) receptor ligand with potent analgesic activity in animal pain models. This proof-of-concept study tested CR4056 efficacy and safety in patients with knee osteoarthritis (OA) and different phenotypes. Design: This is a multicenter, randomized, double-blind, placebo-controlled trial. Knee OA patients with moderate to severe pain received CR4056 (women 100 mg bid; men 200 mg bid) or placebo (both genders) for 14 days. The primary outcome was the change in WOMAC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 27 publications
0
21
0
2
Order By: Relevance
“…CR4056 is an ideal candidate for such analysis: It specifically binds I 2 receptors with no or negligible interactions with over 60 pharmacologically relevant targets (in either binding or functional assays, Rottapharm Biotech, data on file). Moreover, this is the first I 2 ligand able to control pain in humans (Rovati et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CR4056 is an ideal candidate for such analysis: It specifically binds I 2 receptors with no or negligible interactions with over 60 pharmacologically relevant targets (in either binding or functional assays, Rottapharm Biotech, data on file). Moreover, this is the first I 2 ligand able to control pain in humans (Rovati et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This drug displays strong in vivo analgesic properties in several animal models of inflammatory, chronic, and neuropathic pain (Comi et al, ; Ferrari et al, ; Lanza, Ferrari, Menghetti, Tremolada, & Caselli, ; Meregalli et al, ; Siemian, Wang, Zhang, & Li, ). A recent phase II clinical trial of CR4056 in patients with knee osteoarthritis chronic pain demonstrated for the first time the efficacy of an I 2 ligand in humans (Rovati et al, ). The understanding of its pharmacological and molecular mechanisms of action leading to analgesia is therefore highly relevant to evaluate its potential use in human therapies and to clarify the functional pathways activated by I 2 ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the results of this study point towards a selective synergism between CR4056 and morphine for their analgesic activity, thus providing a strong rationale for use of CR4056 as an opioid‐sparing drug in multimodal analgesia. CR4056 is the first I 2 receptor ligand to show analgesic activity in humans (Rovati et al, 2020), which supports clinical development as a non‐opioid analgesic across a broad range of pain indications. Our present findings open a novel development path for CR4056 at low doses.…”
Section: Discussionmentioning
confidence: 87%
“…; CR4056 was suspended in 0.5% hydroxypropylmethyl cellulose (HPMC) and administered orally. The oral route was chosen because CR4056 has good oral availability and is formulated for oral administration in humans (Rovati et al, 2020). Volumes of administration were 5 mlÁkg −1 for CR4056 and naloxone and 2 mlÁkg −1 for morphine.…”
Section: Experimental Design and Drug Treatmentsmentioning
confidence: 99%
“…была показана высокая эффективность фиксированных комбинаций хондроитина и глюкозамина, превосходящая таковую при мототерапии [7]. Учитывая несогласованность мнений экспертов и результатов исследований относительно эффективности SYSADOA, особую актуальность приобретает тезис о том, что когорта больных ОА является фенотипически гетерогенной [8,9]. При этом неоднородность когорты больных реализуется на клиническом, молекулярном и структурном уровнях [10,11,12,13].…”
Section: Introductionunclassified